Valproic acid decreases resuscitation requirements after hemorrhage in a prolonged damage-control resuscitation model. Issue 4 (October 2020) - Biesterveld, Ben E.; Williams, Aaron M.; Kemp, Michael T.; Wakam, Glenn K.; Siddiqui, Ali Z.; O'Connell, Rachel L.; Shamshad, Alizeh; Chtraklin, Kiril; Bhatti, Umar F.; Li, Yongqing; Alam, Hasan B.
Abstract : BACKGROUND: Hemorrhage is the leading cause of preventable death in trauma. Future military conflicts are likely to be in austere environments, where prolonged damage-control resuscitation (p-DCR) may be required for 72 hours before evacuation. There is a need to demonstrate that p-DCR is feasible and to optimize its logistics. Dried plasma (DP) is a practical alternative to conventional blood products in austere settings, and valproic acid (VPA) improves survival in preclinical models of trauma and hemorrhage. We performed the current experiment to study the synergistic effects of VPA and DP and hypothesized that VPA treatment would decrease the fluid resuscitation requirements in p-DCR. METHODS: Female swine were subjected to 50% hemorrhage (associated with 20% survival using non–plasma-based p-DCR) and left unresuscitated for 1 hour to simulate medic response time. They were then randomized to receive VPA (150 mg/kg + DP 250 mL; DP-VPA group; n = 5) or DP alone (DP group; n = 6). All animals were resuscitated to a systolic blood pressure of 80 mm Hg with lactated Ringer according to the Tactical Combat Casualty Care Guidelines for 72 hours, after which packed red blood cells were transfused to simulate evacuation to higher levels of care. RESULTS: The DP-VPA group needed significantly ( p = 0.002) less volume of lactated Ringer to reach and maintain the target systolic blood pressure. This would translate to a 4.3 L volume sparing effect for a 70-kg person. CONCLUSION: Addition of a single dose of VPA significantly decreases the volume of resuscitation required in a p-DCR model. Abstract : Supplemental digital content is available in the text.